A novel integrated thiosulfate-driven denitritation (TDD) and anaerobic ammonia oxidation (anammox) process for biological nitrogen removal - Qian, Jin (2020)
An integrated system by combining the thiosulfate-driven denitritation (TDD) and anaerobic ammonia oxidation (anammox) was established for high-rate biological nitrogen removal (BNR) and less N2O generation under 35 °C. The anammox contribute to 27% nitrogen removal in the system. The anammox activity was enhanced by four times as temperature increased from 20 to 35 °C. The less N2O emission at 35 °C compared with that at 20 °C is attributed to the involvement of anammox (characterized as no N2O generation) function rather than higher N2O reducing rate under the thermophilic condition. The produced NO3− in anammox can be readily reduced by thiosulfate. The results of this study could enlighten us how to induce a high nitrogen degradation activity with lower sludge yield, in the meanwhile to minimize the greenhouse gas emission and the nitrogenous residues in the BNR process.